An on-line inspection method for abrasive distribution uniformity of electroplated diamond wire saw. (November 2021) - Zhao, Yukang; Bi, Wenbo; Ge, Peiqi
Abstract: Electroplated diamond wire saws are widely used in the field of slicing hard and brittle materials. The slicing quality and efficiency are directly affected by the abrasive distribution uniformity of the wire saw. At present, the abrasive distribution uniformity can only be qualitatively analyzed manually. In this paper, the expanded circumferential surface image of the wire saw is obtained by the method of cylindrical unwrapping and image stitching. Then the image is segmented by the Voronoi diagram. On this basis, the quantitative characterization and the online inspection method of the abrasive distribution uniformity are proposed. Finally, the real-time performance of the method is tested through experiments. The results show that under the hardware environment of this paper, this method takes 0.156 s to detect a sampling point, which meets the online detection requirements of the wire saw.